Synchronization of Central-Regional Authority in Integrated Mining Licensing Management - Muhammad Irfan; Subekti Subekti (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
This study aims to juridically analyze the synchronization of central and regional authorities in the management of integrated mining licenses through the Online Single Submission Risk Based Approach (OSS-RBA) system. The problems studied focus on the overlapping authority between the Ministry of Energy and Mineral Resources and the Ministry of Environment and Forestry in the practice of mining licensing, even though an integrated licensing system has been normatively implemented after the enactment of the Job Creation Law. This research uses normative legal research methods with a legislative approach and a conceptual approach. Primary legal materials include Law Number 3 of 2020 concerning Mineral and Coal Mining, Law Number 41 of 1999 concerning Forestry, and Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing, which are analyzed together with secondary legal materials in the form of doctrine and scientific journals. The results of the study show that OSS-RBA has integrated licensing procedures administratively, but has not fully realized substantive synchronization of authority between sectoral agencies, thus potentially causing legal uncertainty. Therefore, it is necessary to harmonize regulations and strengthen the integration of authorities so that the integrated mining licensing system can run effectively and fairly.